The Relationship between Sanitation and Diarrhea in Kabupaten Pidie, Aceh (Used Validity Inference) - Darnas, Y; Yolanda, R (KnE Life Sciences, 2019)
According to World Health Organization (WHO), the world most prevalent issues are illness and death caused by environmental factors such as water, land, and air. The causes contribute to premature death of millions of people, especially infants and children every year. This issue mostly experienced by developing country, including Indonesia, approximately four million infants and children die from diarrhea due to contaminated water and food. Unavailability of solid waste management and domestic wastewater service in the region causes poor sanitation, it results in the high incidence of contaminated water. This study would analyze the relationship between sanitation and diarrhea in Kabupaten Pidie, Aceh using validity inference. Validity refers to the approximate truth of an inference. Valid meant the extent to which relevant evidence supports that inference as bring true or correct. Usually, that evidence comes from both empirical findings and the consistency of these findings with other sources of knowledge, including past finding and theories. Assessing validity always entails fallible human judgments. Validity is not absolute; various degrees of validity can be invoked. In this study from table distribution F, we got F table 3.95 with probability α (5%), df-numerator [(k – 1) = 1] and df-denominator [k(N-1) = 90] and F arithmetic is 5.95269E-09. It means F arithmetic < F table so that, Hypothesis null (Ho) accepted and sanitation have significant effect on diarrhea. Keywords: Diarrhea; inference; Kabupaten Pidie; sanitation; validity